Osteoclasts and CD8 T Cells Form a Negative Feedback Loop That Contributes to Homeostasis of Both the Skeletal and Immune Systems - Zachary S. Buchwald; Rajeev Aurora (Clinical and Developmental Immunology)
There are a number of dynamic regulatory loops that maintain homeostasis of the immune and skeletal systems. In this review, we highlight a number of these regulatory interactions that contribute to maintaining homeostasis. In addition, we review data on a negative regulatory feedback loop between osteoclasts and CD8 T cells that contributes to homeostasis of both the skeletal and immune systems.